2012
DOI: 10.1109/twc.2012.070912.111293
|View full text |Cite
|
Sign up to set email alerts
|

Physical Layer Integration of Private, Common, and Confidential Messages in Bidirectional Relay Networks

Abstract: In order to increase spectral efficiency, it is becoming more and more important that next generation wireless networks wisely integrate multiple services such as transmissions of private, common, and confidential messages at the physical layer. This is referred to as physical layer service integration, and in this paper is being studied for bidirectional relay networks. Here, a relay node establishes a bidirectional communication between two other nodes using a decode-and-forward protocol. This is also known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…As in [16,62,63], we consider two different kinds of power constraints: a total power constraint and a covariance constraint. An input sequence x n = (x 1 , x 2 , .…”
Section: Physical Layer Description and Capacity Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in [16,62,63], we consider two different kinds of power constraints: a total power constraint and a covariance constraint. An input sequence x n = (x 1 , x 2 , .…”
Section: Physical Layer Description and Capacity Resultsmentioning
confidence: 99%
“…Other ongoing research activities on bidirectional relaying and its extensions can be found in [16] where private, common and confidential messages are integrated in the bidirectional relay networks, in [17] where a survey of different processing strategies is provided, in [18] where the efficient integration of bidirectional relaying in a cellular downlink is presented and in [19][20][21] where bidirectional relaying for multiple pairs of nodes is analyzed. Further, bidirectional relaying with an additional private message for the relay in the MAC phase is addressed in [22] and beamforming strategies for multi-antenna bidirectional relaying with analog network coding is presented in [23].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Under discrete memoryless broadcast channel (DMBC) setup, Csiszár and Körner gave a closed-form expression of the maximum rate region that can be applied reliably under the secrecy constraint (i.e., the secrecy capacity region). In recent years, this kind of approach has gained renewed interest, especially that in various multi-antenna scenarios, such as Gaussian broadcast channels [12]- [15], and bidirectional relay channels [16], [17]. In [12], the authors extended the results in [11] to a general MIMO Gaussian case by adopting the channel-enhancement argument.…”
Section: B Related Workmentioning
confidence: 99%
“…The resulting secrecy capacity region is proved to be attainable by combining the secret dirtypaper coding (S-DPC) with Gaussian superposition coding. Furthermore, in [16] and [17], Wyrembelski and Boche amalgamated broadcast service, multicast service and confidential service in bidirectional relay networks, in which a relay adds an additional multicast message for all nodes and a confidential message for only one node besides establishing the conventional bidirectional communication. Nonetheless, the main goal of the aforementioned papers is just to obtain capacity results or to characterize coding strategies that lead to certain rate regions [18].…”
Section: B Related Workmentioning
confidence: 99%